EXPERIMENTAL MODEL OF DISTANCE EDUCATION FUTURE EXPERTS IN HIGHER EDUCATIONAL INSTITUTIONS - Roman Gorbatyuk; Lyudmyla Romanyshyna (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
The paper deals with the use of information and communication technologies at higher educational institutions of Ukraine. Knowledge accumulation and sharing system, which consists of classroom fund, laboratories, workshops, exchange of experience, practical information, research sector, workstation, network forums and chat rooms, electronic resources, information space has been suggested. Distance education process model, based on the general theoretical principles of modeling, according to which the model's characteristics are defined as a pedagogical object, has been substantiated. The model is a complex system of the structural elements, which include: aim, content, functional, organizational and evaluation subsystems. To assess its effectiveness a pedagogical experiment has been carried out on the average level of knowledge retention, time to prepare specialists in a particular subject's content area,  students' participation in the classroom.